What is the diabetic foot? Medical Ontology Essay - Mazza Bruno, Milton E. (Cirugía del Uruguay, 1993)
The starting point of reflection that concerns me is a fact of experience that is superimposed both chronologically and conceptually by a cognitive malaise that appears to me as a problem that i will try to make explicit, show so that at least the contents are revealed of the problem itself